(untitled) (Journal of humanities and social sciences exploratio, 2026)
Curse insults are a linguistic phenomenon embedded in Chinese folk daily life. Their underlying operating mechanism is not merely simple emotional catharsis, but also involves a system of "linguistic sorcery" grounded in traditional belief systems and informal social control technologies. An investigation from the perspective of folklore can unravel the mystery of why such curses exert strong psychological deterrence and social normative effects. The study reveals that their efficacy is based on three interrelated belief systems: the spiritual power of language, sympathetic magic, and the underworld worldview. Functionally, they participate deeply in the construction and maintenance of folk social order through three channels: ethical discipline, conflict mediation, and psychological compensation. Interpreting curse insults as a form of "linguistic sorcery" provides a new micro-perspective for understanding the cultural logic of Chinese folk society.